Industrial Training Management System (INTRAS) / Norizan Mohamad... [et al.] - Mohamad, Norizan; Mohamed@Omar, Hasiah; Ishak, Siti Nurul Hayatie; Amron, Mohd Talmizie; Abdul Latiff, Mohd Hanapi (2018)
Industrial training refers to the placement of students at selected organizations in their respective field of study. Usually several parties are involved i.e. the students, the industrial training coordinator, the academic supervisor and the industry supervisor. However, most activities are still performed manually including student’s placement, reporting and assessment. In addition, integration among all parties is still lacking. The industrial training process consumes a great deal of time and energy particularly in acquiring the placements for all the students. First, the process places a heavy workload on the industrial training coordinator since the coordinator needs to manage the entire document required for every student. Unfortunately, the documentation is still being managed manually, heavily dependent on papers. Second, the coordinator must handle all the communication to and from the students and the industry regarding the current status of each application. Third, sometimes it takes time for companies to confirm the availability of the internship position, although the students have contacted them personally. The objectives of the research project are (1) to identify the requirements for managing industrial training process and (2) to design and develop the Industrial Training Management System (INTRAS). This research design employs a design and creation strategy that focuses on developing an artifact. The research process will follow the Systems Development Life Cycle (SDLC) methodology that will employ the Rapid Development (RAD) model. The outcome from this research project is an online industrial training management system which is a web-based system. In this system, the industrial training coordinator manages related activities of industrial training process. It will be used by all the related parties i.e. the students, the industrial training coordinator, the academic supervisor and the industry supervisor.